Could Road Structures Impact the Avian Community? A Study Case from the South Coast Remained Forest in Malang Region, East Java Province, Indonesia: Impact of Road Structures on Avian Community - Nurrofik, Agus; Hakim, Luchman; Septiadi, Luhur; Kurniawan, Nia (Journal of Tropical Life Science, 2024)
The remaining tropical forest on the south coast of the Malang region is one of the secluded areas that served as an important habitat for its biodiversity, particularly for avians. Nevertheless, the presence of the road structure that crosses over the forest might impact avian communities, which needs to be investigated. The avian survey was conducted to investigate the diversity, community profiles, abundance, and feeding guild based on two different ecosystem patches (on the roads versus outside the road structures) during January–April 2022. The audiovisual encounter methods were performed during the surveys on a total of ten sampling points. Avian species were identified using field guides where the conservation status was based on the national regulation (P106 KLHK), CITES, and IUCN Redlist. The comparison through the avian community based on species richness was analyzed using Venn Diagrams and predicted using rarefaction and interpolation curves on INEXT packages. Additionally, the comparison of sizes of avian abundance was investigated using the α-diversity parameter index, and the feeding guild was determined by five diet guilds. In total, 2536 individuals from 67 species, 34 families, and 13 orders were found during the survey. The avian communities were richer outside the road structure, but their abundance qualitatively reveals that both different ecosystem patches showed relatively good condition. Overall, road structures generate both positive (unique habitat patches) and negative (physical barriers that could disrupt natural ecological processes) impacts on avian diversity. In light of these, sustainable management and conservation action plans were urgently needed to prevent the negative effects on avian communities posed by the road structure.